Right Middle Cerebral Artery Intracranial Stent for Intracranial Atherosclerotic Disease - Abdul Rahim, Ezamin; Mohd Yaakob, Mohd Naim; Kamis, Mohd Fandi Al-Khafiz; Muda, Ahmad Sobri; Md Noh, Mohamad Syafeeq Faeez (The Interventionalist Journal, 2022)
The article briefly discusses the basis of why the intracranial stent was deployed during mechanical thrombectomy.